First record of ectoparasitic ciliates, of genus Trichodina (Ciliophora: Trichodinidae) parasiting cultured Oranda Gold Fish (Carassius auratus auratus L.) in India - Saha, Mandira; Bandyopadhyay, Probir Kumar; Göçmen, Bayram (Zootaxa, 2017)
Ornamental fish culture is considered as one of the most important source of home entertainment, because of its diversity and beauty of picturesque colors. Trichodiniasis of fishes causing harm and economic losses in this fish industry. There are many records of trichodinids ectoparasites infesting fish have been found throughout the World, but no such attempt has been made to study the parasitic group infesting ornamental fish, preferably oranda goldfish (Carassius auratus auratus L.) in India. A parasitological search in some ornamental fish farms have been revealed for the first time the occurrence of trichodinid species previously described so far from the oranda goldfish in India. They are Trichodina reticulata, Trichodina mutabilis, Trichodina acuta, Trichodina ngoma, Trichodina nandusi and Trichodina domergui. These parasites have not been reported earlier from the oranda goldfish in India. The paper deals with the diversity, distribution and taxonomic descriptions of these six trichodinid species based on the wet silver nitrate impregnated observations along with new host, locality and prevalence of infestation.